Functional magnetic resonance imaging of kidneys - Siniša Ristić (Биомедицинска истраживања, 2019)
Tendency of modern diagnostic visualization development in biomedicine is focused on the integration of detection and quantification of molecular, functional and morphological events in the biological systems. The increasing number of patients with chronic kidney disease stimulated the development of new diagnostic methods. The development of magnetic resonance technology encouraged the use of functional magnetic resonance imaging of kidneys in both scientific research and clinical practice. The paper presents the basic characteristics of the functional magnetic resonance imagining and the possibilities for its use in the examination of kidney functions.
Keywords: kidneys; magnetic resonance imagining; visualization; function; kidney disease